DISEASE INTENSITY AND INCIDENCE OF PEST AND DISEASES ON EGGPLANT (Solanum melongena L.) IN WEDOMARTANI, SLEMAN REGENCY, SPECIAL REGION OF YOGYAKARTA : INTENSITAS DAN INSIDENSI PENYAKIT PADA HAMA DAN PENYAKIT TANAMAN TERONG (Solanum melongena L.) DI WEDOMARTANI, KECAMATAN SLEMAN, YOGYAKARTA - Indriyani, Melissa; Naila Rahma Syahriyani; Shafa Kautsar Imayana (Agrofarm: Jurnal Agroteknologi, 2025)
Eggplant (Solanum melongena L.) is one of the horticultural commodities in Indonesia. Eggplant productivity in Indonesia tends to increase every year. Although production continues to show an increase every year, market demand for eggplant has not been fully met. This study aims to identify pests and diseases, as well as assess appropriate control strategies to support the increase in purple eggplant productivity in a sustainable manner. This study was conducted at the Rd. Blotan Sono, Wedomartani, Sleman Regency, Special Region of Yogyakarta. The observation method applied was a survey method or direct observation in the field. Sampling was carried out using random sampling. Koksi beetle being the most dominant pest with the severe intensity of attack, while yellowing disease, powdery mildew, and brown stink bugs show low intensity. In general, these conditions indicate the need for proper pest management through the implementation of Integrated Pest Management (IPM), including land sanitation, pruning of infected parts, crop rotation, use of resistant varieties, and selective biological and chemical control to maintain the productivity of eggplants.